(untitled) (International Journal of Engineering and Computer Science, 2018)
In the past wireless LANS and Cellular networks were used for communication In case of wireless networks if the nodes are mobile then Manets (mobile ad-hoc networks) can be used for communication. If the distance between the nodes increases it is not possible to communicate so to remove this limitation the idea of opportunistic networks was developed because they can only work when distance is less. This network makes it possible to communicate between nodes irrespective of their distance and the type of node. An opportunistic network tries to remove the statement of physical end-to-end connectivity while providing connectivity opportunities to pervasive devices when they are not directly connected to the Internet. Enveloping devices, can opportunistically exploit their mobility and contacts for data delivery. In this paper we are going to compare three basic protocols used in this kind of network based on some common parameters.